The impact of cross-delisting from the U.S. on firms’ financial constraints - Loureiro, Gilberto (2020)
We investigate the impact of cross-delisting on firms’ financial constraints. We find that firms that cross-delisted from a U.S. stock exchange face stronger post-delisting financial constraints than their cross-listed counterparts, as measured by investment-to-cash flow and cash-to-cash flow sensitivities. Following a delisting, the sensitivity of investment to cash flow increases significantly, and firms also tend to save more cash out of cash flows. These effects are mainly driven by cross-delisted firms from countries with weaker investor protection and are more predominant after the passage of Rule 12 h-6 (of 2007), which made it easier for foreign firms to leave U.S. markets.